Discarded Cigarette Butts Attract Females and Kill the Progeny of Aedes albopictus - Dieng, Hamady; Rahman G. M., Saifur; Abu Hassan, Ahmad; Che Salmah, Md Rawi; Boots, Michael; Satho, Tomomitsu; Wan Fatma, Zuharah; Nik, Fadzly; Abdulaziz, Althbyani; Miake, Fumio; Zairi, Jaal; Sazaly, Abubakar (The American Mosquito Control Association, 2011)
Discarded cigarette butts (DCB) waste occurs worldwide, pollutes landscapes, is unsightly, and results in added debris removal costs. There is, therefore, a great deal of current interest in making use of DCBs in beneficial ways. Despite evidence that DCBs are harmful to water fleas (Daphnia magna), which breed in aquatic environments as do mosquito larvae, their impact on dengue vectors is unknown. We examined whether Aedes albopictus alters its ovipositional responses, larval eclosion, and development in response to presence of DCBs in its habitats. We found oviposition activity in DCB-treated water similar to that of control water and that ovipositional activity in DCB solutions steadily increased over time as those solutions aged to 10 days. Larval eclosion was initially suppressed on day 1 in DCB solution, but increased thereafter to levels similar to control larval eclosion rates. The DCB–water solutions produced significantly higher mortality in both 1st and 2nd instars over control larvae for several days after initial exposure. Mortality rates decreased sharply 3 to 5 days postexposure as DCBs continued to decompose. We found increased survival rates during late development, but daily input of fresh DCBs prevented most young larvae from completing development. Taken together, these observations suggest that decomposing did not deter gravid Ae. albopictus females from ovipositing in treated containers and that DCB solutions had larvicidal effects on early instars. Our results are discussed in the context of DCB use to control container-breeding Ae. albopictus, a competent dengue vector in Asia and other parts of the world.